2020
DOI: 10.1212/wnl.0000000000010192
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathologic features associated with basal forebrain atrophy in Alzheimer disease

Abstract: Objective:To study the neuropathological correlates of cholinergic basal forebrain atrophy as determined using ante-mortem MRI in the Alzheimer’s disease (AD) spectrum.Methods:We determined associations between basal forebrain (BF) volume from antemortem MRI brain scans and post-mortem assessment of neuropathological features, including neuritic plaques, neurofibrillary tangles (NFT), Lewy body (LB) pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 49 publications
6
28
0
Order By: Relevance
“…In the analysis of amyloid stratified subgroups, our results are in accordance with previous studies reporting significant volume loss in MCI + and ADD + ( Grothe et al, 2014 , Kerbler et al, 2015 , Teipel et al, 2014a ). Previous combined volumetric and amyloid-PET studies in MCI ( Grothe et al, 2014 , Kerbler et al, 2015 , Teipel et al, 2014a ) had suggested that cBF volumetry was strongly associated to amyloid burden and this was recently supported by evidence from an imaging-neuropathological association study ( Teipel et al, 2020 ). Therefore, we had expected a stronger connection of cBF volume to amyloid status even in preclinical cases.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In the analysis of amyloid stratified subgroups, our results are in accordance with previous studies reporting significant volume loss in MCI + and ADD + ( Grothe et al, 2014 , Kerbler et al, 2015 , Teipel et al, 2014a ). Previous combined volumetric and amyloid-PET studies in MCI ( Grothe et al, 2014 , Kerbler et al, 2015 , Teipel et al, 2014a ) had suggested that cBF volumetry was strongly associated to amyloid burden and this was recently supported by evidence from an imaging-neuropathological association study ( Teipel et al, 2020 ). Therefore, we had expected a stronger connection of cBF volume to amyloid status even in preclinical cases.…”
Section: Discussionmentioning
confidence: 80%
“…Further studies suggested that in preclinical and prodromal stages of AD, cBF volume may be even more sensitive to early degenerative changes than hippocampal or entorhinal cortex atrophy ( Kilimann et al, 2014 , Schmitz et al, 2016 ). In vivo MRI-PET studies and a recent imaging-neuropathological association study suggest that cBF atrophy may be associated with cortical amyloid pathology in prodromal and dementia stages of AD ( Grothe et al, 2014 , Kerbler et al, 2015 , Teipel et al, 2020 ).…”
Section: Introductionmentioning
confidence: 97%
“…Associations between neuroimaging measures and clinical outcomes can rarely be expected to be strictly linear and will generally depend on the functional consequences of the neurodegenerative process that is indexed by the macro-and microstructural neuroimaging alterations. A recent imaging-neuropathology association study found that CBF volume on structural MRI correlated with the extent of Lewy body pathology in the nucleus basalis of Meynert, but not with semi-quantitative assessments of cell loss in this region [29]. This indicates that the neuroimaging measures may also pick up relatively subtle tissue changes in response to neurodegenerative pathology [30].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, understanding the underlying neural substrates is important for developing treatments. The basal forebrain (BF) is a brain region which degenerates in dementia [5][6][7] and is implicated in the negative effects of sleep disruption on vigilance and cognition 8,9 . Previous studies demonstrated that the BF controls cortical fast oscillations that underlie attention [10][11][12] and revealed the important role of cholinergic neurons [13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Neurotoxic lesions of the BF impair attention in rodents 26,27 and in primates 28,29 . Furthermore, BF degeneration is associated with cognitive deficits, including attention, in Alzheimer's and Parkinson's dementias [5][6][7] . Deficits in attention caused by BF lesions in animals and cognitive deficits associated with dementias have generally been associated with loss of BF cholinergic neurons and their effects in the cortex 13,[30][31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%